2019
DOI: 10.3389/fimmu.2019.01696
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Depression and Fatigue

Abstract: Depression and fatigue are conditions responsible for heavy global societal burden, especially in patients already suffering from chronic diseases. These symptoms have been identified by those affected as some of the most disabling symptoms which affect the quality of life and productivity of the individual. While many factors play a role in the development of depression and fatigue, both have been associated with increased inflammatory activation of the immune system affecting both the periphery and the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
298
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(322 citation statements)
references
References 143 publications
(150 reference statements)
15
298
1
8
Order By: Relevance
“…Cytokines are soluble intercellular signaling molecules that are involved in the pathophysiology of several mental disorders through affecting neurotransmitter synthesis, release, and reuptake [79], as well as regulating BDNF expression [80]. In regard to mental disorders, there is a growing body of research investigating the possible cross-talk between pathological alterations in sleep patterns [81], depression [82], and anxiety disorders [83] and inflammation-related diseases that involve increased inflammatory cytokines release. On the other hand, different studies have also shown that a deficit of anti-inflammatory cytokines, such as transforming growth factor-β1 (TGF-β1), can contribute to the pathogenesis of depressive disorders [84].…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Cytokines are soluble intercellular signaling molecules that are involved in the pathophysiology of several mental disorders through affecting neurotransmitter synthesis, release, and reuptake [79], as well as regulating BDNF expression [80]. In regard to mental disorders, there is a growing body of research investigating the possible cross-talk between pathological alterations in sleep patterns [81], depression [82], and anxiety disorders [83] and inflammation-related diseases that involve increased inflammatory cytokines release. On the other hand, different studies have also shown that a deficit of anti-inflammatory cytokines, such as transforming growth factor-β1 (TGF-β1), can contribute to the pathogenesis of depressive disorders [84].…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 99%
“…For instance, cytokines have been suggested as predictors of the antidepressant effect of exercise 13 , and meta-analysis has shown that certain types of antidepressants reduce pro-inflammatory factors such as C-reactive protein, tumor necrosis factor-α and interleukin −1β, showing some interaction between antidepressant medication, depression and inflammation 14 . Another review showed that the effects of antidepressant drugs have been consistently linked to decreased inflammation 15 . However, despite the extensive research into cytokines in this area, a related family of immune system-derived signaling proteins, the chemokines, has been relatively neglected 7 .…”
mentioning
confidence: 99%
“…For example, treating multiple sclerosis with powerful antiinflammatories was associated with reduction of depressive symptoms (68). Conversely, treatment of hepatitis C with interferon alpha, a powerful activator of an inflammatory response, induces depression in roughly 20% of patients (72,73). Work over the last decade has characterized the nature of the inflammatory processes underlying depression and its possible influence on the brain.…”
Section: Inflammationmentioning
confidence: 99%
“…Briefly, cytokines are elevated in a portion of patients suffering from depression. In particular, tumor necrosis factor alpha (TNFa), interleukin-2 (IL-2), interleukin-6 (IL-6), interleukin-13 (IL-13), interleukin-18 (IL-18), Creactive protein (CRP), chemokine-2 (CCL2), and chemokine-11 (CCL11) are elevated in depression based on multiple metaanalyses (68,71,73). But how inflammatory cytokines induce depressive symptoms remain incompletely understood.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation